Africanidades e eurocentrismos em pelejas culturais e educacionais no fazer-se histórico do Cabo Verde - Moniz, Elias Alfama Vaz (2007)
This study emphasizes educational matters in Cape Verde that takes place in specif historical contexts, specially during the 1990s. From this research, discussions are emerged under cultural and political tensions, as well as the cape verdian identity and its typical elements, such as the Creole, mother tangue of Cape Verde. It implies, as well, strategies of domination and control from social groups in various contexts, during the colonial regime and post-colonial period. The reflections about educational proposals in Cape Verde, during the mentioned period, allow us to understand the tensions produced in the encounter of human groups with different social experiences and cultural backgrounds